An Analytic Hierarchy Process Based Approach for Evaluating Feasibility of Offshore Wind Farm on the Colombian Caribbean Coast - Ospino-Castro, Adalberto; Robles-Algarín, Carlos; Mangones-Cordero, Amanda; Romero-Navas, Sharys (International Journal of Energy Economics and Policy, 2023)
Planning a wind power generation project is intricate, considering the number of variables to be careful in the acceptable zone selection for its siting. One of the difficulties of developing a wind farm is finding the most satisfactory location to build it; this can take years of feasibility studies. The main objective of this research is to use the Analytic Hierarchy Process (AHP) to prioritize a group of criteria and sub-criteria as decision-making support for the selection of suitable areas in which implementing wind energy projects in the Colombian Caribbean Sea. The criteria to be applied in this study were selected based on the most recurrently employed criteria in other research papers and the experience of the authors. Thus, a hierarchical structure with 4 criteria (technical, environmental, social, and economic) and 14 subcriteria was implemented. All criteria were prioritized using the methodology proposed by AHP, for which 10 experts with experience in offshore wind projects were consulted, through a form designed with a matrix structure. The results allowed prioritizing a set of criteria necessary for offshore energy planning projects, in which the criteria of Protected Area (19.62%), Wind Speed (13.84%) and Military Areas (9.79%) were the most relevant.